A robust role for motor cortex - Lopes, Gonçalo; Nogueira, Joana; Dimitriadis, George; Menendez, Jorge Aurelio; Paton, Joseph J.; Kampff, Adam R. (Frontiers in Neuroscience, 2023)
The role of motor cortex in non-primate mammals remains unclear. More than a century of stimulation, anatomical and electrophysiological studies has implicated neural activity in this region with all kinds of movement. However, following the removal of motor cortex, rats retain most of their adaptive behaviours, including previously learned skilled movements. Here we revisit these two conflicting views of motor cortex and present a new behaviour assay, challenging animals to respond to unexpected situations while navigating a dynamic obstacle course. Surprisingly, rats with motor cortical lesions show clear impairments facing an unexpected collapse of the obstacles, while showing no impairment with repeated trials in many motor and cognitive metrics of performance. We propose a new role for motor cortex: extending the robustness of sub-cortical movement systems, specifically to unexpected situations demanding rapid motor responses adapted to environmental context. The implications of this idea for current and future research are discussed.